2015
DOI: 10.1039/c5ay01312g
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolic profiling study of endometriosis by using wooden-tip electrospray ionization mass spectrometry

Abstract: A high throughput metabolite fingerprinting tool based on wooden-tip electrospray ionization mass spectrometry (WT-ESI-MS) has been established for the serum metabolic profiling study of endometriosis with little sample pre-treatment, no chromatography and instrument cycle times of less than 5 min. Serum samples from endometriosis patients and healthy controls were analyzed by direct WT-ESI-MS with a high resolution ESI-Q-TOF-MS. The resulting data were analyzed by multivariate data analysis. MS/MS experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…So far, various substrates including metal materials, porous materials, functionalized materials, and biological materials have been successfully developed as tip‐ESI for direct sample analysis. For example, wooden tip‐ESI‐MS has been used for direct analysis of biofluid samples such as blood, urine, and oral fluid . In addition, high‐throughput screening of clinical samples were also achieved using this kind of tip‐ESI methods such as paper spray ionization and coated blade spray …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, various substrates including metal materials, porous materials, functionalized materials, and biological materials have been successfully developed as tip‐ESI for direct sample analysis. For example, wooden tip‐ESI‐MS has been used for direct analysis of biofluid samples such as blood, urine, and oral fluid . In addition, high‐throughput screening of clinical samples were also achieved using this kind of tip‐ESI methods such as paper spray ionization and coated blade spray …”
Section: Introductionmentioning
confidence: 99%
“…For example, wooden tip-ESI-MS has been used for direct analysis of biofluid samples such as blood, urine, and oral fluid. [33][34][35] In addition, high-throughput screening of clinical samples were also achieved using this kind of tip-ESI methods such as paper spray ionization and coated blade spray. 36,37 However, both Bio and Neo are highly hydrophilic analytes 38 ; it is found that the interaction between analytes and hydrophilic tips (eg, wooden tip) could reduce the detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The slim and hard wooden tips are very convenient for sampling, and the techniques could be used for analysis of samples of various forms. [32][33][34][35][36][37] In this study, WT-ESI-MS was further developed for rapid detection of adulterated drugs in three common categories of herbal dietary supplements, i.e., tranquilizer, aphrodisiac and weight-loss products. Thirty-three commonly adulterated drugs were analyzed with their standards, and a database containing their ESI-MS and ESI-MS/MS spectra was established.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The development of ESI techniques with solid substrates has taken place since ESI with copper wires was developed in the late 1990s. ESI using wooden tips (common toothpicks) is readily available with very low costs and can be directly mounted on a nanoESI device without hardware modication, 18 showing that wooden-tips could be used for many applications due to their convenient sampling and rapid analysis, e.g., pharmaceutical analysis, 23 metabolite analysis, 24,25 forensic analysis, 26 and plant identication. ESI using wooden tips (common toothpicks) is readily available with very low costs and can be directly mounted on a nanoESI device without hardware modication, 18 showing that wooden-tips could be used for many applications due to their convenient sampling and rapid analysis, e.g., pharmaceutical analysis, 23 metabolite analysis, 24,25 forensic analysis, 26 and plant identication.…”
Section: Introductionmentioning
confidence: 99%